Without management there is no diffusion and access: historical and conceptual aspects of Canadian and Brazilian archival science - Barros, Thiago Henrique Bragato [UNESP] (My University, 2020)
We work historically and conceptually with the development of practices related to diffusion and access to archives, building a comparison between Canadian and Brazilian reality from a theoretical point of view, systematizing the possible relations between these countries. It is concluded that access and diffusion are linked to State policies and their legal provisions.
Sin gestión no hay difusión y acceso: aspectos históricos y conceptuales de la archivología canadiense y brasileña
Sem gestão não há difusão e acesso Aspectos histórico-conceituais da arquivística canadense e brasileira
Keywords: access; archival science; Brazil; Canada; diffusion